Taxonomy of Tabanus trivittatus species-group (Diptera: Tabanidae), with description of five new species - Carmo, Daniel D. D.; Henriques, Augusto L. (Zootaxa, 2019)
The group of species related to Tabanus trivittatus include horse flies with striped abdomens and partially bare, inflated, subcallus. Herein we describe five new species and raise the number of valid species from 15 to 20, four of which occur in Brazil: T. albocapilus sp. n., T. dorsorufus sp. n., T. mackerrasi sp. n., T. macrocerus sp. n. and one that occur in Brazil, Bolivia and Peru: T. noncallosus sp. n. We also modified the keys from Fairchild (1976) for both sexes and briefly discuss the female genitalia.